Language Attrition in Bilingual Children: Implications for Early Foreign Language Teaching - Medved Krajnović, Marta (2008)
The article gives a brief overview of the language attrition research as a primarily psycholinguistic phenomenon studied within disciplines of second language acquisition (SLA) and bilingualism. An example of first language attrition within the overall development of Croatian (L1) – English (L2) childhood bilingualism is presented. On the basis of the research findings, implications are drawn for the process of early foreign language teaching.
Projekt MZOS
ENG